Possibilities in Blockchain technology application - Bačević Jelena (Trendovi u Poslovanju)
Block chain technology is becoming more and more important as it is being applied in many fields of business. Blockchain serves as a continuing book of records enabling transactions to develop in decentralized circumstances. Although it is a relatively new technology (first theoretical work dates from 2008), developed and applied primarily in payment systems (Bitcoin), it appeared that its potentials are far beyond it. Within the period from its beginning until the present day, this technology has been considerably improved, applied algorithms perfected and accommodated to contemporary business environment. Research in the field of application concerning this technology was made on the basis of available literature and papers published in relevant journals. The paper represents a comprehensive review of possibilities in Blockchain technology application in contemporary business environment, its benefits and shortcomings as well as security problems appearing in theory and practice. This paper also deals with the analysis of possible trends in the mentioned field.